EFEKTIFITAS BUS TRANS SARBAGITA TRAYEK KOTA – GWK DALAM MENGURANGI KEMACETAN DI KOTA DENPASAR DAN KABUPATEN BADUNG - I Made Agus Putrayasa; Ni Kadek Sri Maharani (Politeknik Negeri Bali, 2014)
Public service is the fulfillment of desires and needs of the community by the state. The purpose of public service is basically satisfy the people. Public service is a very important for people to get ease in their activities. Bus Trans Sarbagita is one of public service in the field of transport owned by the provincial government of Bali to stretch Kota - GWK. This study aims to determine the effectiveness of State Route Bus Trans Sarbagita Kota - GWK which in terms of accessibility, capacity, timeliness, tariffs / pricing, as well as safety and comfort. In collecting the data, researchers used a structured interview with a means of questionnaires and observation. Data was collected through questionnaires by respondents. The Trans Sarbagita Bus Kota - GWK Route considered effective in terms of accessibility and capacity even Bus Trans Sarbagita Route Kota - GWK is considered to be very effective when viewed in terms of safety and comfort as well as the rates / prices. However Bus Trans Sarbagita Route Kota - GWK considered ineffective in terms of timeliness because Bus Trans Sarbagita Route Kota - GWK often exposed to congestion on the Patung Dewa Ruci thus making their journey longer time compared to using a personal vehicle.